The Prognostic Association of Prostate MRI PI-RADS™ v2 Assessment Category and Risk of Biochemical Recurrence after Definitive Local Therapy for Prostate Cancer: A Systematic Review and Meta-Analysis - Rajwa, Pawel; Mori, Keiichiro; Huebner, Nicolai A; Martin, Darryl T; Sprenkle, Preston C; Weinreb, Jeffrey C; Ploussard, Guillaume; Pradere, Benjamin; Shariat, Shahrokh F; Leapman, Michael S (The Journal of urology, 2021)
PURPOSE: Although the Prostate Imaging-Reporting and Data System™ version 2 (PI-RADS™ v2) is a reliable diagnostic tool for significant prostate cancer, less is known about the prognostic significance of the structured reporting scheme for estimating oncologic outcomes after treatment. We aimed to synthesize the available evidence regarding the association of PI-RADS v2 score and risk of biochemical recurrence (BCR) among patients undergoing primary definitive treatment for prostate cancer. MATERIALS AND METHODS: We systematically queried the PubMed® and Web of Science™ databases to identify studies addressing the association between the PI-RADS v2 and treatment outcomes. We included studies through November 2020 that assessed the independent prognostic significance of PI-RADS v2. After assessing risk of bias and quality, we conducted a formal meta-analysis to estimate the pooled effects of prostate magnetic resonance imaging (MRI) classification on the risk of BCR. RESULTS: We identified 9 and 7 eligible studies including 2,274 and 1,215 patients for the systematic review and meta-analysis, respectively. Eight were conducted in the context of radical prostatectomy and 1 post-radiation. Among patients treated with radical prostatectomy, higher PI-RADS v2 scores were significantly associated with risk of BCR (pooled HR 3.06, 95% CI 2.16-4.33; p <0.01). There was no significant heterogeneity among studies. For all studies, PI-RADS v2 score remained significantly associated with BCR (pooled HR 3.19, 95% CI 2.28-4.45; p <0.01). CONCLUSIONS: Prostate MRI findings assessed with the PI-RADS v2 classification were independently associated with risk of BCR after definitive local therapy, primarily based on data from radical prostatectomy. These findings support the prognostic significance of MRI, in addition to its role in prostate cancer diagnosis.
Keywords: prostatektomie; Neoplasm Recurrence, Local; Prognosis; Magnetic Resonance Imaging; Male; Prostate-Specific Antigen; lidé; Humans; Prostatectomy; prostatic neoplasms, prognosis; Prostatic Neoplasms; magnetic resonance imaging; lokální recidiva nádoru; prostatický specifický antigen; Risk Assessment; mužské pohlaví; nádory prostaty; prostata; Brachytherapy; brachyterapie; Kallikreins; hodnocení rizik; kalikreiny; prognóza; Prostate; magnetická rezonanční tomografie